Answer:
-1.25
Step-by-step explanation:
Given that,
Initial quantity demanded = 300
Initial price = $0.60
New quantity demanded = 500
New price = $0.40
Mid-point method is used here,
Average quantity demanded:
= (Initial quantity demanded + New quantity demanded) ÷ 2
= (300 + 500) ÷ 2
= 400
Average price = (Initial price + New price) ÷ 2
= ($0.60 + $0.40) ÷ 2
= $0.5
Therefore,
Change in quantity demanded:
= (New quantity demanded - Initial quantity demanded) ÷ Average quantity demanded
= (500 - 300) ÷ 400
= 0.5
Change in price:
= (New price - Initial price) ÷ Average price
= ($0.40 - $0.60) ÷ $0.5
= -0.4
Hence, the price elasticity of demand is as follows:
= Change in quantity demanded ÷ Change in price
= 0.5 ÷ -0.4
= -1.25